Investigating the Reactivity of Investors' Decisions on Selling Shares Based on Fundamental Analysts' Recommendations: Evidence from Stock Exchange Investors in Iran’s Fars Province - Mojtaba Rostami Noroozabad; Haniyeh Arian Asl; Khalil Abbasi Museloo (تحقیقات مالی)
Objective: Most economic and financial theories, according to the "rational economic man" theory, assume that when investing, investors consider all aspects and make completely rational decisions. However, the concept of a rational person remains ambiguous since human decisions deviate from the standard assumptions of economics. Individual stocks are recommended for purchase or sale by financial experts and stock market analysts and are followed by a large number of individual and institutional investors. Analysts provide information of varying quality to various groups of investors, as a result of the differences in these groups' characteristics and the information available to them, each group behaves differently. Since each of these groups may uniquely rely on the market, understanding the basis of the collective behavior of different investor groups can lead to a better understanding of price fluctuations. This study investigates how investors in the Iranian province of Fars react to the recommendations of fundamental analysts when selling shares.Methods: In this study, the laboratory-field method was employed to design and execute two experiments involving a total of 315 investors. The participants were divided into control and experimental groups, and the study focused on investigating the presence or absence of the tendency effect in the Iranian stock market within the control group. The impact of analysts' reasoning and recommendations on investor decisions and behavior was evaluated in the experimental group.Results: The first experiment showed that the Iranian stock market is influenced by a tendency effect. The findings of the second experiment revealed that under good market conditions, investors kept winning stocks with both strong and weak analyst recommendations. Under difficult market conditions, investors were less likely to sell losing stocks (with negative returns) with excellent expert recommendations but more eager to sell with weak analyst recommendations.Conclusion: The purpose of this study was to examine how the recommendations of fundamental analysts impact the decision-making of stock exchange investors in the Fars province of Iran regarding the sale of stocks. Accordingly, 315 Tehran Stock Exchange investors from various cities in Fars province were divided into two experimental groups (each with 130 participants) and a control group (including 55 participants). The research findings indicated that given favorable market circumstances and the lucrative share position, with both the analyst's strong and weak recommendation (based on keeping the share), people resist selling and begin to keep the share. Furthermore, despite the analyst's strong recommendation, people stop selling and risk keeping the shares due to unfavorable market conditions and the losing stock's position (with additional information to support the recommendation to sell the shares). Unlike earlier studies, this study investigated the impact of fundamental analysts' recommendations on investors' decisions to sell shares depending on probability.